Relative bioavailability of diclofenac potassium from softgel capsule versus powder for oral solution and immediate‐release tablet formulation. Issue 1 (5th October 2015) - Bende, Girish; Biswal, Shibadas; Bhad, Prafulla; Chen, Yuming; Salunke, Atish; Winter, Serge; Wagner, Robert; Sunkara, Gangadhar
Abstract: The oral bioavailability of diclofenac potassium 50 mg administered as a soft gelatin capsule (softgel capsule), powder for oral solution (oral solution), and tablet was evaluated in a randomized, open‐label, 3‐period, 6‐sequence crossover study in healthy adults. Plasma diclofenac concentrations were measured using a validated liquid chromatography–mass spectrometry/mass spectrometry method, and pharmacokinetic analysis was performed by noncompartmental methods. The median time to achieve peak plasma concentrations of diclofenac was 0.5, 0.25, and 0.75 hours with the softgel capsule, oral solution, and tablet formulations, respectively. The geometric mean ratio and associated 90%CI for AUCinf, and Cmax of the softgel capsule formulation relative to the oral solution formulation were 0.97 (0.95–1.00) and 0.85 (0.76–0.95), respectively. The geometric mean ratio and associated 90%CI for AUCinf and Cmax of the softgel capsule formulation relative to the tablet formulation were 1.04 (1.00–1.08) and 1.67 (1.43–1.96), respectively. In conclusion, the exposure (AUC) of diclofenac with the new diclofenac potassium softgel capsule formulation was comparable to that of the existing oral solution and tablet formulations. The peak plasma concentration of diclofenac from the new softgel capsule was 67% higher than the existing tablet formulation, whereas it was 15% lower in comparison with the oral solution formulation.